FORMATION OF TOP JOB SKILLS OF TOMORROW AMONG COMPUTER ENGINEERING AND INFORMATION TECHNOLOGIES UNDERGRADUATE STUDENTS IN THE PROCESS OF LEARNING ENGLISH (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The main aim of the study was to investigate Computer Engineering and Information Technologies undergraduate students’ attitude towards the most important job skills of tomorrow and to provide methodology for their enhancing in the process of learning English. To collect data essential for developing methodology aimed at enhancing top job skills of tomorrow in the process of learning English, 295 Computer Engineering and Information Technologies undergraduate students aged from 17 and 21 were selected to take part in the web-based survey. In total, research sample was presented by 64 female students and 231 male students. The team of researchers developed the educational content of the English elective course targeted at developing top job skills of tomorrow among undergraduate students. Taking into account the fact that English holds great didactic potential for developing knowledge, skills and aptitudes among students of different specialties at higher education institutions necessary for reaching success in the future, the educational content of the English elective course is oriented towards increasing motivation to master English among undergraduate students of the mentioned specialties, on the one hand, and to boost the identified job skills of tomorrow, on the other hand. The realization of the proposed educational content is based on the integration of the fundamental principles of action-oriented, competence-based, mastery-based and project-based approaches. Considering English as an efficient medium of instruction we can suggest the following idea: upgrading the educational content can provide endless opportunities for professional development of undergraduate students. To be exact, on their way of gaining professionally valuable knowledge and skills generally subdivided into two groups (soft skills and hard skills) they are involved in the activities that could guarantee the development of abovementioned skills. Thus, the created English elective course could serve as an example to follow.